2010
DOI: 10.1103/physrevb.82.075313
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-dimensional spectral diffusion of type-II excitons in InP/InAs/InP core-multishell nanowires

Abstract: Spectral diffusion of type-II excitons in InP/InAs/InP core-multishell nanowires ͑CMNs͒ and type-I excitons in an InAs/InP single quantum well ͑SQW͒ was studied by means of time-resolved and spectrally resolved photoluminescence. InP/InAs/InP CMNs in hexagonal symmetry are made of six facets and six edges which work as two-dimensional quantum wells and one-dimensional quantum wires, respectively. At 5 K type-II excitons lose their energy in two stages. In the first stage, two-dimensional spectral diffusion tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…All peaks exhibit the same linear dependence on the excitation power without any clear blue shift indicating a type I band alignment. This is in contrast with earlier reports done by another group where optical investigations suggested a type II alignment [13,14]. Moreover, this study indicates the absence of the state filling effect's signature allowing the attribution of the higher energy side peaks to the excited state emission.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…All peaks exhibit the same linear dependence on the excitation power without any clear blue shift indicating a type I band alignment. This is in contrast with earlier reports done by another group where optical investigations suggested a type II alignment [13,14]. Moreover, this study indicates the absence of the state filling effect's signature allowing the attribution of the higher energy side peaks to the excited state emission.…”
Section: Resultscontrasting
confidence: 84%
“…In particular, monolithic integration of emitters on silicon is still in great demand. While several studies have already been reported on the growth andz optical properties of InP/InAs/InP core-shell NWs on InP substrates [12][13][14], the study of the growth of such heterostructured NWs on Si substrates has not yet been reported. In this context, we have studied the growth of InP/InAs/InP NWs grown on Si substrates by VLS-assisted solid source MBE (ssMBE).…”
Section: Introductionmentioning
confidence: 98%
“…Polarized photoluminescence from single wurtzite InP/InAs/InP core-multishell nanowires Yasuaki Masumoto,1,a͒ The photoluminescence from single InP/InAs/InP core-multishell nanowires ͑CMNs͒ was highly linearly polarized in perpendicular to the nanowire long axis. Taking account of dielectric confinement of light field, we found the internal optical dipole squared perpendicular to the nanotube long axis d 0x 2 is larger than that parallel to the axis d 0z 2 by two orders of magnitude.…”
mentioning
confidence: 99%
“…Nanotubes work as quantum wells and quantum wires and emit bright photoluminescence ͑PL͒ in the near infrared region. 1 Another unique feature of InP/InAs/InP CMNs is the wurtzite structure instead of zincblende structure for both InAs and InP bulk crystals. 2,3 The crystal field as well as spin-orbit interaction in the wurtzite structure split the top valence band into ⌫ 9 ͑A͒-state, ⌫ 7 ͑B͒-state, and ⌫ 7 ͑C͒-state.…”
mentioning
confidence: 99%
“…Due to the small radial dimensions of the NWs the design of NW heterostructures is not limited by strain as in conventional planar molecular beam epitaxy (MBE) or metal-organic-vapor-phase-epitaxy (MOVPE) thus enabling the fabrication of a wide variety of radial heterostructures as e.g. GaAs/AlGaAs 7 , GaAs/GaP 12 and InP/InAs 13 core-shell NWs. Also axial NW heterostructures 7,14 become feasible that comprise segments of different semiconductor material with nanometer thickness along the NW [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%